Preoperative Anxiety Assessment in Adult Patients Undergoing Elective Surgeries: A Cross-Sectional Observational Study - Acharya, Santosh; Gurung, Renu; Parajuli, Basudev (Journal of Institute of Medicine Nepal, 2020)
Introduction Anxiety is the subjective unpleasant feeling of dread over something unlikely to happen. The incidence of preoperative anxiety ranges from 32% to 76.7%. We aimed to measure the preoperative anxiety level using Amsterdam Preoperative Anxiety and Information Scale questionnaire and clinical rating scale given by attending anesthesiologist / anesthesia residents. Methods It was cross-sectional observational study conducted in wards. We enrolled 110 adult patients planned for elective gynecological and gastrointestinal surgeries. After taking informed written consent, principal investigator interviewed the patient, one day prior to surgery in wards using a structured questionnaire of Amsterdam Preoperative Anxiety and Information Scale. Demographics characters were recorded. The attending anesthesia residents (blinded to patient response) performed preanesthetic assessment, provided their subjective rating about patient anxiety and need for information using Clinical Rating Scale. Results Out of 110 patient, 57(51.81%) were found to have higher anxiety level. Comparing the APAIS score with various factors, we found younger age, female gender, unemployed status, higher level of education, adverse events in previous surgery and higher grade of surgery was associated with higher anxiety score. Comparing APAIS with Clinical Rating Score, there was poor correlation. Conclusion The incidence of preoperative anxiety is high (51.81%) in adult patients undergoing elective surgery. During the preoperative anesthetic checkup, APAIS can be used as a screening tool. It provides relevant information on the presence of preoperative anxiety and need for information, which helps to achieve patient satisfaction and better outcome.